The End of History. Or, is it? Circularity versus Progress in Caryl Phillips' The Nature of Blood - Ángeles De la Concha (Miscelánea: A Journal of English and American Studies)
In the wake of the revisionist thinking of the Enlightenment and its selflegitimising narratives, history is no longer accepted as linear time projected into a future ever open to gradual progress and freedom. This breakdown of linearity together with the acknowledgement of the discipline's textual fabric and discursive nature are accountable for a new, apocalyptic version of the ultimate stage of historical development termed the end of history, in which circularity and bleak repetition are now rampant. In this essay I explore one of the ways in which the central grand story of Western civilisation has been questioned through the narratives of novelists belonging to alternative races and, therefore, hitherto excluded from canonical historical versions. For this purpose, I have chosen The Nature of Blood (1997) by Caryl Phillips, as a dramatisation of the endless recurrence of subjugations which, according to Foucault, need to replace history's selfcomplacent narrative of ideal significations and indefinite teleologies.